SISTEM INFORMASI KATALOG BUKU DIGITAL (E-KATALOG) BERBASIS WEB UNTUK PENINGKATAN EFEKTIVITAS LAYANAN PERPUSTAKAAN SMPN 41 JAKARTA - Kausar Andhika Sugiharto; Yuliana; Asyid Nabilul Azhar; Bagas Irawan; Danish Arfandi Lubis; Luqman Hakim; Muhammad Arif Maulana; Muhammad Yusuf Bastian; Muhammad Zaidan Faqih; Putra Mahesa; Rizky Ramadhan Putra Darmadi (Abdi Jurnal Publikasi, 2026)
The rapid development of information technology has significantly transformed information management systems, including library services in educational institutions. Conventional library catalog systems that rely on manual recording and physical book searches often result in inefficiency, limited accessibility, and low service effectiveness. This community service activity aims to design and implement a web-based digital book catalog (e-Catalog) system to improve the effectiveness of library services at SMPN 41 Jakarta. The system was developed using a structured software architecture based on the Laravel framework, which applies the Model–View–Controller (MVC) pattern to ensure scalability, maintainability, and security. Data collection methods included observation, interviews, and documentation involving librarians and library users. The results indicate that the implemented e-Catalog system facilitates faster book searching, improves data accuracy, enhances accessibility for users, and optimizes librarians’ administrative tasks. The adoption of a web-based digital catalog also supports digital transformation in school libraries by aligning with modern information system practices. Overall, the implementation demonstrates that a Laravel-based e-Catalog system can significantly enhance the effectiveness and efficiency of library services in secondary educational institutions.